Effects of two feedback interventions on end-of-life outcomes in nursing home residents with dementia: A cluster-randomized controlled three-armed trial. (March 2018) - Boogaard, Jannie A; de Vet, Henrica CW; van Soest-Poortvliet, Mirjam C; Anema, Johannes R; Achterberg, Wilco P; van der Steen, Jenny T
Background: Despite increased attention for palliative care in dementia, recent studies found burdensome symptoms and unmet family caregiver needs in the last phase of life. Feedback is being used to improve the quality of palliative care, but we do not know how effective it is. Aim: To assess the effect of two feedback strategies on perceived quality of end-of-life care and comfort in dying nursing home residents with dementia. Methods: In a cluster-randomized controlled trial, the End-of-Life in Dementia–Satisfaction With Care and the End-of-Life in Dementia–Comfort Assessment in Dying scales were completed by bereaved family caregivers of residents with dementia of 18 Dutch nursing homes. Two feedback strategies, generic feedback with mean End-of-Life in Dementia-scores and feedback with individual (patient-specific) End-of-Life in Dementia-scores, were compared to no feedback provided. The intervention groups discussed End-of-Life in Dementia-ratings in team meetings and formulated actions to improve care. Multi-level analyses assessed effects. Results: A total of 668 families rated the End-of-Life in Dementia–instruments. Compared to no feedback, the generic strategy resulted in lower quality of end-of-life care in unadjusted ( B  = −1.65, confidence interval = −3.27; −0.21) and adjusted analyses ( B  = −2.41, confidence interval = −4.07; −0.76), while there was no effect on comfort. The patient-specific strategy did not affect the quality of end-of-life care, but it increased comfort in unadjusted analyses (only, B  = 2.20, confidence interval = 0.15; 4.39; adjusted: B  = 1.88, confidence interval = −0.34; 4.10). Conclusion: Neither feedback strategy improved end-of-life outcome. Perhaps, skills to translate the feedback into care improvement actions were insufficient. Feedback with favorable family ratings might even have triggered opposite effects. Trial number: NTR3942.